Vigilância e big data em saúde: a questão ética no uso de dados pessoais em publicações científicas nas Ciências da Saúde - Beloni, Aneli (2021)
Immersed in a universe where we produce data that is collected all the time for different purposes, this research starts from Information Science studies to identify whether and how the ethical issue is addressed in scientific publications in the field of Health Sciences, with regard to extraction and use of personal data in the context of surveillance and big data. The research is bibliographic and exploratory. The methodology explores content analysis based on the Bardin model with research data collected at Pubmed, a source of information specialized in Health Sciences. The result of the analysis identified records of concern with ethical issues in the technological universe of big data and surveillance and pointed out that the ethics on which the Health Sciences are based is pretty much legalistic, which differs from the understanding of ethics as a science of morals. The research points to the ethics of health data as a fertile ground for further research and defends critical information literacy as a way to alert the population to the benefits and harms surrounding the use of their personal data by third parties.